Varied macronutrient uptake by plants as an effect of different fertilisation schemes evaluated by PCA. (2nd January 2020) - Jakubus, Monika; Bakinowska, Ewa
ABSTRACT: Nowadays the role of organic amendments is increasing as a valuable source of nutrients. Organic fertilisation improves general soil fertility but concomitantly slow nutrient release and the risk of low efficiency of nutrient utilisation by crops is underlined. Thus the study investigates the influence of soil amendment with mineral, organic and mineral–organic fertilisation on macronutrient uptake by plants: camelina ( Camelina sativa L.), white mustard ( Sinapis alba L.) and spring barley ( Hordeum vulgare L.) cultivated on light soils. A three-year pot experiment was conducted in PVC pots. The individual fertilisers were applied at 70 and 170 kg N ha −1 . The study clearly demonstrated that independently of the fertilisation type, their doses equivalent to 170 kg N ha −1 caused significantly higher uptake of all analysed nutrients by plants in comparison to those grown in the soil enriched with fertilisers with lower doses of nitrogen. The performed statistical analysis (a multi-factorial analysis of variance and the Principal Component Analysis) confirmed genetic variance in macronutrient accumulation by plants cultivated in crop rotation, whereas on average white mustard absorbed the highest amounts of nutrients except for Mg. In addition, the application of the PCA analysis facilitated the determination of the interrelationships between nutrients.